Encyclopedic dictionary of cults, sects, and world religions - Nichols, Larry A.; Mather, George A.; Schmidt, Alvin J.; Van Gorden, Kurt.; Mather, George A. (Grand Rapids, Mich. : Zondervan, 2006)
"This updated dictionary explores a variety of religious beliefs"--Provided by publisher.
Rev. ed. of: Dictionary of cults, sects, religions, and the occult. 1993.
Includes bibliographical references (p. 477-521) and index.
Keywords: Religions -- Dictionaries; Cults -- Dictionaries; Sects -- Dictionaries